2006
DOI: 10.1097/01.mcg.0000225668.53673.e6
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Abnormalities as a New Manifestation of Nonalcoholic Fatty Liver Disease: Echocardiographic and Tissue Doppler Imaging Assessment

Abstract: Nonalcoholic fatty liver disease (NAFLD) is linked to the metabolic syndrome. The aim of the present study is to determine the effect of the metabolic syndrome on left ventricular (LV) geometry and function using as a model patients with NAFLD. Thirty-eight patients with NAFLD, less than 55 years of age and with a normal exercise test, were compared with an age and sex-matched control group. Patients with diabetes mellitus, hypertension, and body mass index>40 were excluded. A complete echocardiographic study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
113
0
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(128 citation statements)
references
References 45 publications
10
113
0
5
Order By: Relevance
“…Interestingly, after correction for well-known cardiometabolic risk factors (gender, age, visceral obesity, IFG/diabetes and hypertension) severe fibrosis maintained its link not only with the parameters of cardiac geometry (left atrial volume, LVM/H 2.7 , PWT and RWT), but also with the indices of diastolic (lateral TDI e', E/e', E/A ratio) and systolic (EF) function. These results expand previous reports in small cohorts of NAFLD patients [10][11][12][13], reporting a significant impairment in cardiac structure and function, as assessed by echocardiography or MRI, in clinically diagnosed NAFLD patients compared with subjects without fatty liver. Along this line, our results fit with the evidence for an association between liver injury and intima-media thickness [2], another early cardiovascular alteration, also present in NAFLD patients.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Interestingly, after correction for well-known cardiometabolic risk factors (gender, age, visceral obesity, IFG/diabetes and hypertension) severe fibrosis maintained its link not only with the parameters of cardiac geometry (left atrial volume, LVM/H 2.7 , PWT and RWT), but also with the indices of diastolic (lateral TDI e', E/e', E/A ratio) and systolic (EF) function. These results expand previous reports in small cohorts of NAFLD patients [10][11][12][13], reporting a significant impairment in cardiac structure and function, as assessed by echocardiography or MRI, in clinically diagnosed NAFLD patients compared with subjects without fatty liver. Along this line, our results fit with the evidence for an association between liver injury and intima-media thickness [2], another early cardiovascular alteration, also present in NAFLD patients.…”
Section: Discussionsupporting
confidence: 88%
“…Specifically, studies in small cohorts of subjects at high [10,11] or low [12] cardiometabolic risk highlighted the association of an ultrasonographic diagnosis of NAFLD, after adjustment for metabolic confounders, with a significant impairment in echocardiographic diastolic function compared to non-NAFLD cases. Along this line, a recent study on a small cohort of NAFLD patients reported significant changes in cardiac structure and function as assessed by MRI, in the absence of metabolic changes or overt cardiac disease [13].…”
Section: Introductionmentioning
confidence: 99%
“…The main cross-sectional [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] and prospective [11,[32][33][34][35][36][37][38][39][40][41][42][43] studies on the association between NAFLD and intermediate markers of CVDor clinical outcomes are shown in Tables 1 and 2 of the Electronic supplementary material. NAFLD, endothelial dysfunction, early carotid atherosclerosis and left ventricular dysfunction NAFLD is associated with circulatory endothelial dysfunction [16,17], a marker of early atherosclerosis. Compared with non-steatotic controls, non-diabetic patients with NAFLD show a significant decrease in brachial artery flow-mediated vasodilation, which is related to the severity of NAFLD histology, independently of age, sex, BMI and HOMA-IR [16].…”
Section: Evidence Linking Nafld With Cvdmentioning
confidence: 99%
“…Similarly, patients with NAFLD, also in the absence of obesity, hypertension and diabetes, exhibit echocardiographic features of early left ventricular dysfunction [18] and impaired energy metabolism as measured by cardiac 31 P magnetic resonance spectroscopy [19].…”
Section: Evidence Linking Nafld With Cvdmentioning
confidence: 99%
“…Considering the influence of liver fat on metabolic health and the association of nonalcoholic fatty liver disease (NAFLD) with features of the metabolic syndrome 24 , others have looked at NAFLD patients and demonstrated subclinical myocardial systolic and diastolic dysfunction in the presence or absence of type 2 diabetes (T2DM) 25,26 .…”
Section: Introductionmentioning
confidence: 99%